2016
DOI: 10.1111/cmi.12587
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between inflammatory mediators and miRNAs in Helicobacter pylori infection

Abstract: Summary Helicobacter pylori cause chronic inflammation favouring gastric carcinogenesis, and its eradication may prevent malignant transformation. We evaluated whether H. pylori infection and its eradication modify the expression of inflammatory mediators in patients with chronic gastritis. Furthermore, we assessed whether microRNAs modulate inflammatory pathways induced by H. pylori and identified miRNA–gene interaction networks. mRNA and protein expression of TNFA, IL6, IL1B, IL12A, IL2 and TGFBRII and miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…Therefore, H. pylori infection may inhibit AHR and AHRR expression in the stomach, and the in vitro and in vivo results supported this speculation. H. pylori infection stimulated stomach cells to produce proinflammatory factors 32 , 33 , and these cytokines exerted provital roles in the pathogenesis of H. pylori infection-associated gastric diseases, including gastritis and gastric cancer 34 , 35 , 36 , 37 . The current study demonstrated that silencing of AHR or AHRR promoted TNF, IL-8 and IL-1β secretion in human stomach cells after coculture with H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, H. pylori infection may inhibit AHR and AHRR expression in the stomach, and the in vitro and in vivo results supported this speculation. H. pylori infection stimulated stomach cells to produce proinflammatory factors 32 , 33 , and these cytokines exerted provital roles in the pathogenesis of H. pylori infection-associated gastric diseases, including gastritis and gastric cancer 34 , 35 , 36 , 37 . The current study demonstrated that silencing of AHR or AHRR promoted TNF, IL-8 and IL-1β secretion in human stomach cells after coculture with H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…At this point, it might be interesting to speculate on how reduced SLC5A8 expression in host cells may benefit H. pylori . Indeed, this pathogen has been shown to modulate host gene expression in ways that favor host infection (Matsushima et al, 2011 ; Kim et al, 2012 ; Hanada and Graham, 2014 ; O'Ryan et al, 2015 ; Rossi et al, 2016 ). As mentioned in this manuscript, SLC5A8 is implicated in the control of short-chain fatty acid uptake, which in turn modulates the expression of cell cycle control and pro-inflammatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…While the pathogenetic mechanisms underlying the effects of a H. pylori on airway disorders remain to be determined, they may involve chronic inflammation promoted by persistent infection with a H. pylori (30,31). It is well-known that a H. pylori colonization of the gastric mucosa stimulates the release of various pro-inflammatory factors, including cytokines and eicosanoids.…”
Section: Fev1 Fvc Vcmax ---------------------------------------------mentioning
confidence: 99%